Application of extended care based on the PRISMS sheet for patients with chronic obstructive pulmonary disease (基于PRISMS表的延续性护理在慢性阻塞性肺疾病患者中的应用) - WANGYUAN Jingmei (王袁婧美); LAI Wei (来薇); WEI Min (魏敏); LI Huayi (李华艺) (中西医结合护理)
Objective To investigate the effect of extended care based on the PRISMS sheet on improving the self-efficacy and health status of patients with chronic obstructive pulmonary disease (COPD). Methods A total of 202 COPD patients were randomly divided into a control group (n=102) and an intervention group(n=102). Both the two groups were treated with conventional extended care. In the intervention group, patient's key concerns were obtained based on the PRISMS form and targeted intervention guidance was provided. The COPD self-efficacy scale(CSES) and COPD assessment test (CAT) were used to evaluate patient self-efficacy and health status. Results After the intervention, the CSES score of the two groups was significantly higher than that before the intervention (P<0. 01), and the CSES score of the intervention group was significantly higher than that of the control group (P<0. 01). After the intervention, the CAT score was significantly reduced, but there was no significant difference in CAT score between two groups (P>0. 05) . Conclusion Extended care based on the PRISMS sheet can effectively improve the self-efficacy of COPD patients and improve their health of patients. (目的 探讨基于患者报告通知自我管理支持表(PRISMS)的延续性护理在提升慢性阻塞性肺疾病患者自我效能和健康状况方面的作用。方法 202例慢性阻塞性肺疾病患者随机分为对照组(n=102)和干预组(n=100)。2组均实施常规延续护理, 干预组在此基础上实施基于PRISMS表的护理干预, 全面获得患者重点关注问题并进行针对性指导。采用慢性阻塞性肺疾病自我效能量表(CSES)及CAT量表评估患者自我效能水平及健康状况。结果 干预后2组患者CSES评分较干预前提高(P<0. 01), 且干预组CSES评分高于对照组(P<0. 01)。干预后2组患者CAT得分较干预前降低, 但组间比较差异无统计学意义(P>0. 05)。结论 基于PRISMS表的延续性护理能有效提高慢性阻塞性肺疾病患者的自我效能水平, 改善患者健康状况。)